PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN BPJS KETENAGAKERJAAN BEKASI KOTA - Muhammad Amien Firdaus; Ella Siti Chaeriah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
The purpose of this study is to analyze the effect of motivation and work discipline on employee performance of BPJS Ketenagakerjaan Bekasi Kota. This research is included in the category of causal associative research using a quantitative approach. The population in this study were all employees of the BPJS Ketenagakerjaan Bekasi Regional Office, totaling 46 people and all of them were sampled, because the numbers were relatively small. Methods of data analysis using partially and simultaneous linear regression. The results showed that partially and simultaneous motivation and work discipline had a positive and significant effect on employee performance of BPJS Ketenagakerjaan Bekasi Kota.